2010
DOI: 10.1071/hc10054
|View full text |Cite
|
Sign up to set email alerts
|

Introducing point-of-care testing into a rural hospital setting: thematic analysis of interviews with providers

Abstract: INTRODUCTION: Hauora Hokianga Enterprises Trust, an integrated Primary Health Organisation (PHO), which provides primary and intermediate/secondary care to a remote rural community, introduced point-of-care (POC) testing at Rawene Hospital in June 2008. Previously, all laboratory tests were undertaken in Whangarei, with a one to three day turn-around for results. This study aimed to identify the perceived impact of POC testing on clinicians and the community. METHOD: Face-to-face interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Community hospitals provide a wide range of services, covering the whole spectrum of care provision, from preventative [2021] and primary care [2223], through to outpatient services [242526], inpatient medical care [2728], surgery [2930], minor injury [31] and accident and emergency care [2232]. Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new and innovative types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing [23], fracture clinics [33] or chemotherapy [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community hospitals provide a wide range of services, covering the whole spectrum of care provision, from preventative [2021] and primary care [2223], through to outpatient services [242526], inpatient medical care [2728], surgery [2930], minor injury [31] and accident and emergency care [2232]. Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new and innovative types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing [23], fracture clinics [33] or chemotherapy [34].…”
Section: Resultsmentioning
confidence: 99%
“…Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new and innovative types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing [23], fracture clinics [33] or chemotherapy [34]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of intangible benefits has been reported separately [5] and includes: clinicians being able to appropriately assess and provide patient care without moving patients unnecessarily-thereby reducing stress and costs on patients and families; improved access to appropriate care for an isolated and high needs Maori community; improved job satisfaction for clinicians; improved communication and integration of patient care between hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study, reported elsewhere [5], examined in-depth understanding of the effects of the introduction of POC testing on clinicians and the community. The present paper reports analyses of quantitative data collected to measure changes in clinical decisions (diagnostic certainty and patient management including decisions around admission, discharge and inter-hospital transfer) associated with POC test use.…”
Section: Introductionmentioning
confidence: 99%